Acaricide resistance and genetic affinities of some selected populations of Tetranychus urticae Koch in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science (Horticultural) in Entomology at Massey University - Ong, S. H. (Massey University, 1973)
A study of resistance to acaricides in a number of populations of the two-spotted spider mite, Tetranychus urticae, in New Zealand had been carried out. Natural genetic and cytoplasmic incompatibilities between populations were also investigated with a view to possible biological control of the pest. Facets of acaricide resistance that were studied included multi-resistance, cross-resistance, negatively correlated resistance and the inheritance of resistance. Chemicals used included an organophosphate representative (parathion-methyl), a carbamate (formetanate), an ungrouped compound (tricyclohexyltin hydroxide) and an organochlorine (dicofol). Cross-resistance was demonstrated between parathion-methyl and formetanate in five populations obtained from widely separate areas of New Zealand. The resistance to parathion of three strains was found to be inherited as a single dominant character and transmissible by both sexes. Cytoplasmic factors (or nucleo-cytoplasmic interactions) and minor genes were found to contribute slightly to the expression of total resistance. No resistance to tricyclohexyltin hydroxide (Plictran) and dicofol (Kelthane) was detected. High degrees of incompatibility (haploid egg lethality) were observed in the hybrids of crosses between the various populations. Chromosomal rearrangements in balanced, heterozygous conditions, in conjunction with the cytoplasm, were considered to be important factors determining the interpopulational sterilities. The interpopulational incompatibility phenomenon was found to be multi-factorial and not associated with the resistance factor. The egg mortalities of some backcross series which remained constantly high in spite of several crossings, implicated that the introduction of normal males to a resistant mite population in an enclosed area (e.g. in a glasshouse) might be a worthwhile proposition in the integrated control of spider mites. Backcross hybrids, on allowing to multiply randomly, were capable of forming new gene combinations, leading consequently to the formation of new strains which were genetically different from the original parents used in the backcross series.
Keywords: Spider mites; Biological control